Activating a teaching-learning philosophy : a practical guide for educators - Grise-Owens, Erlene; Miller, J. Jay; Owens, Larry W. (CSWE Press, 2018)
This how-to manual provides a structured framework for developing a comprehensive teaching learning philosophy from articulation through implementation to evaluation and then reactivation. Using professional literature and teaching learning experiences, the authors provide pragmatic steps for using a grounded philosophy to inform, engage, and assess teaching learning. They advocate an integrated teaching learning philosophy to promote ongoing commitment, engaged competency, and meaningful purpose in practice for educators.